“I can't enjoy my studies, I'm stressed” Effect of Academic Stress on Positive Mental Health In Students College - HERDIAN; Totok, Haryanto (International Journal of Scientific Research and Management (IJSRM), 2021)
The world has experienced a tremendous impact over the past two years due to the COVID-19 pandemic. One of the impacts is the change in the learning system from offline classes to online classes. Not a few studies say that online learning impacts students' psychology, one of which is academic stress. This study examines the effect of academic stress on positive mental health in college students during the COVID-19 pandemic. A total of 76 psychology students in Central Java, Indonesia, participated in this study. The results show a significant effect of academic stress on positive mental health in students during online learning during the COVID-19 pandemic. The implications of the results of this study are discussed in detail